UPAYA PEMBENTUKAN KARAKTER PESERTA DIDIK MELALUI MANAJEMEN PENDIDIKAN BERBASIS RELIGIUSITAS DI SMP YAPIDA CISAYONG KABUPATEN TASIKMALAYA - Jani Sanjari T (HASBUNA : Jurnal Pendidikan Islam, 2023)
This research method uses a qualitative approach, the location is at SMP YAPIDA Cisayong Tasikmalaya, the data collection technique is by participatory observation, interviews, and documentation. Analyzing the data interactively, while checking the validity of the data using credibility, transferability, dependability and confirmability. Education planning based on Religiosity management at SMP YAPIDA Cisayong Tasikmalaya through formulating the school's vision and mission, holding meetings with teachers, holding meetings with parents/guardians of students, planning to implement habituation. Its implementation starts from a program determined at the beginning of the year, then it is carried out starting from daily, weekly and incidental activities. After students are accustomed to carrying out all activities at school, students are able to apply religious behavior wherever they are, they are accustomed to noble moral behavior. The inhibiting factor is the lack of maximum cooperation of all school stakeholders and the lack of support from the parents of the students and the supporting factors are the school's vision and mission, the human resources of educators meet the standards and the school environment is close to Islamic boarding schools even though it is not a school structure.